2021
DOI: 10.1098/rsos.201264
|View full text |Cite
|
Sign up to set email alerts
|

Common cuckoo females remove more conspicuous eggs during parasitism

Abstract: Avian obligate brood parasites gain an advantage by removing the eggs of the cuckoos who have already visited the nest, which can increase the chances of survival for their offspring. Conversely, to prevent their eggs from being picked up by the next parasitic cuckoo, they need to take some precautions. Egg mimicry and egg crypsis are two alternative strategies to prevent the parasitized egg from being picked up by another parasitic cuckoo. Here, we tested whether the egg crypsis hypothesis has a preventative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In contrast, we believe that the rejection of model egg in this study is more likely to be a continuation of egg recognition behavior, where the removal of non‐conspecific model eggs from neighboring nests is an expression of egg recognition stimuli. A similar study on the Oriental Reed Warbler in another population during the egg stage also found that they also rapidly reject model eggs in neighboring nests (Wang, Zhang, et al., 2021 ). Previous studies have suggested that hosts can fine‐tune their egg recognition abilities in response to external parasitism risk (Lindholm & Thomas, 2000 ; Zhang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In contrast, we believe that the rejection of model egg in this study is more likely to be a continuation of egg recognition behavior, where the removal of non‐conspecific model eggs from neighboring nests is an expression of egg recognition stimuli. A similar study on the Oriental Reed Warbler in another population during the egg stage also found that they also rapidly reject model eggs in neighboring nests (Wang, Zhang, et al., 2021 ). Previous studies have suggested that hosts can fine‐tune their egg recognition abilities in response to external parasitism risk (Lindholm & Thomas, 2000 ; Zhang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 78%
“…The former is widely recognized as an effective strategy evolved to counteract the host's egg recognition ability and the interaction process proceeds and constitutes escalating coevolution (Soler, 2014 ). The crypsis hypothesis is used to explain exceptional cases where non‐mimetic parasitic egg would survive in host nests because of dim coloration which is cryptic enough to avoid detection by the host (Antonov et al., 2011 ; Wang, He, et al., 2021 ; Wang, Zhang, et al., 2021 ; Yang et al., 2023 ), secondary parasite (Gloag et al., 2014 ; Thorogood et al., 2017 ; Wang et al., 2020 ) or predator (Mason & Rothstein, 1987 ). Previous studies have found that some parasites lay dark‐colored parasitic eggs and mostly use hosts with darker nesting environments, presumably using darker nesting environments to hide darker parasitic eggs as a response to host egg recognition and rejection, in line with the crypsis hypothesis (Langmore et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explain these exceptions, the cryptic egg hypothesis was proposed to deduce that a non-mimetic cuckoo egg would survive in host nests because it had dim coloration as an adaptive response to predation pressure or secondary parasitism (i.e. egg removal) by other cuckoos [14,15,18], or simply because it was cryptic enough to avoid detection by the host [20,21]. These assumptions were not mutually exclusive, and we hypothesized that no single assumption could fully account for the evolutionary patterns observed, especially for the first two mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the cryptic egg hypothesis was proposed to suggest an alternate coevolutionary trajectory of adaptation in parasite eggs [15,16]. This hypothesis demonstrated that the use of crypticity rather than mimicry of a parasite egg evolved as an adaptive trait, because it would favour the parasite egg (i) escaping from being recognized by the host [17], (ii) avoiding replacement by other parasites during egg-laying [14,18] or (iii) reducing predation risk by a predator [19]. Crypticity consists of two aspects: egg darkness and nest similarity (similarity to host nest appearance).…”
Section: Introductionmentioning
confidence: 99%